Posterior Spiracles of Fourth Instar Larvae of Four Species of Phlebotomine Sand Flies (Diptera: Psychodidae) under Scanning Electron Microscopy - Pessoa, Felipe Arley Costa; Queiroz, Raul Guerra de; Ward, Richard Douglas (Memórias do Instituto Oswaldo Cruz, 2000)
In the present study, posterior spiracles of laboratory-reared fourth instar larvae of Lutzomyia longipalpis, L. migonei, L. lenti, and L. whitmani (Diptera: Psychodidae) of the State of Ceará, Brazil, were examined under scanning electron microscopy. The number of papillae of spiracles examined varied according to the species examined, but no intraspecific differences were found. The importance of this structure to sand fly larva identification and phylogeny is commented.
Keywords: Diptera; Lutzomyia Longipalpis; Phlebotominae; Psychodidae; Animals; Disease Carrier; Larva; Psychodidae; Microscopy, Electron, Scanning; Ultrastructure; Animal; Insect Vectors; Larva; Microscopy, Electron, Scanning; Psychodidae